Efficacy of Variable versus Fixed-Rate Infusion of Phenylephrine during Caesarian Section: a study from Rawalpindi, Pakistan - Irfan, Shahzada; Yaqub, Khan Muhammed; Yasin, Bilal; Bashir, Muhammad Shahzad; Hussain, Mansoor; Beg, Mirza Hamid (Pakistan Armed Forces Medical Journal, 2025)
Objective: To compare the efficacy of variable and fixed-rate infusion regimens of phenylephrine in prophylaxis of maternal hypotension during elective Cesarean section.Study Design: Quasi-experimental studyPlace and Duration of Study: Department of Obstetrics and Gynecology at the Pak Emirates Military Hospital (PEMH) Rawalpindi, Pakistan from Feb to Jul 2021.Methodology: Study included 94 pregnant women all of whom were planned to undergo non-emergent Caesarian section at ≥37 weeks of gestation. Those who were >35 years old or had any history of medical comorbidities were excluded from the study. A fixed infusion regimen was injected to Group-A (n=47) at a continuous rate of 0.75µg/kg/minute, while Group-B (n=47) received a variable phenylephrine dosage, starting at 0.75µg/kg/minute which was increased to 0.9µg/kg/minute in case of hypotension, or reduced to 0.4µg/kg/minute in event of reactive hypertension. Furthermore, 100µg bolus was given if hypotension was noted intraoperatively. Any incidence of hypotension or other adverse events was recorded.Results: Mean age for variable infusion and fixed infusion groups were 24.6±4.7 and 26.2±4.6 years respectively. Both the groups exhibited a significant role of phenylephrine in hypotension prophylaxis. A slightly lower incidence of hypotension was observed during fixed rate infusion (25.5%) as compared to the variable rate (38.3%). No significant intergroup variability was reported (p=0.954). Headaches and nausea/vomiting were the most prevalent postoperative complaints, with a slightly higher incidence in the variable rate group.Conclusion: Both variable and fixed rates of phenylephrine infusion yielded a similar outcome during spinal anesthesia in elective C-section.